Personal Branding Mubalig Di Media Sosial - Anjani, Mike Ayu; Rahman, Encep Taufik (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2025)
This research aims to find out Ustaz Handy Bonny’s personal branding, managing preaching content and understanding the impact of personal branding on the reputation and acceptance of his preaching. The research method used is qualitative descriptive using Goffman's theory which defines impression management as a process where a person is in a social situation. can verbally and non-verbally control the appearance of clothing, words, and gestures to improve their impression in front of others. The research results show that Ustaz Handy Bonny succeeded in building a solid personal branding by utilizing visual aesthetics, message consistency, and using musical elements that are relevant to the content of his preaching. Keywords : Personal Branding; Mubalig; Social Media; Instagram.